Stochastic optimal control for sampled‐data system under stochastic sampling. Issue 11 (1st July 2018) - Sun, Haoyuan; Chen, Jie; Sun, Jian
Abstract : In this study, the problem of designing a stochastic optimal controller for sampled‐data systems whose sampling interval is subjected to a certain probability distribution is addressed. To design the controller, the Kronecker product operation and the Vandermonde matrix were introduced. A design method of the stochastic optimal controller is proposed. It is shown that the controller guarantee that the closed‐loop system has exponentially mean square stability. Finally, the simulation results illustrate the effectiveness and practicability of the proposed method.